If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1 + 2x + -4 + 3x + -9 + 4x + -16 + 5x + -25 = 0 Reorder the terms: -1 + -4 + -9 + -16 + -25 + x + 2x + 3x + 4x + 5x = 0 Combine like terms: -1 + -4 = -5 -5 + -9 + -16 + -25 + x + 2x + 3x + 4x + 5x = 0 Combine like terms: -5 + -9 = -14 -14 + -16 + -25 + x + 2x + 3x + 4x + 5x = 0 Combine like terms: -14 + -16 = -30 -30 + -25 + x + 2x + 3x + 4x + 5x = 0 Combine like terms: -30 + -25 = -55 -55 + x + 2x + 3x + 4x + 5x = 0 Combine like terms: x + 2x = 3x -55 + 3x + 3x + 4x + 5x = 0 Combine like terms: 3x + 3x = 6x -55 + 6x + 4x + 5x = 0 Combine like terms: 6x + 4x = 10x -55 + 10x + 5x = 0 Combine like terms: 10x + 5x = 15x -55 + 15x = 0 Solving -55 + 15x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '55' to each side of the equation. -55 + 55 + 15x = 0 + 55 Combine like terms: -55 + 55 = 0 0 + 15x = 0 + 55 15x = 0 + 55 Combine like terms: 0 + 55 = 55 15x = 55 Divide each side by '15'. x = 3.666666667 Simplifying x = 3.666666667
| (6x-7/10)=9 | | 5(x-3)-30=30 | | 4+2(3x-6)=5-3(2x+1) | | 2+4(5x-6)=9-5(2x+1) | | 8x-7(-88/41)=13 | | N=60t-6t^2 | | 7x-y=15 | | -5(13+7y)-6y=23 | | 11x-99=11 | | 8x+6=6(x+7) | | 0.3x-5=0.1(x+10) | | 3x^2-39x=0 | | Y-9-y+5=8y | | 1200=7v*v+300 | | y=7v*v+300 | | .4x+.6y=24 | | 13m^2+39m=0 | | sx+ty=u | | z^4-1=0 | | x-9/2-3=x-8/3 | | 11x/14-9=x/7+36 | | x/4+x/5=9/20 | | 0=-16t^2+vt+c | | 2n/3-7/13=31/39 | | 4c+1=32 | | x/4-3=-8 | | 9(z+3)-2(z-4)=3(z-4)+3(z-1) | | 9(z+3)-2(z-4)=3(z-1) | | 2x^3+x-18=0 | | -9x+4y=14 | | X^2=y+12 | | 8x=36x |